2016
DOI: 10.1177/0007650315586179
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Governments in the Business and Society Debate

Abstract: The role of governments in business and society (B&S) research remains underexplored. The generally accepted principle of voluntarism, which frames responsible business conduct as an unregulated subject under managerial discretion, accounts for this gap. Paradoxically, there are sufficient acknowledgments in academia and practice on different roles of governments. The present article identifies three broad topics for research, addressing (a) the paradox between the principle of voluntarism and the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 42 publications
(46 reference statements)
0
61
0
Order By: Relevance
“…Thus, we are witnessing a case of self-extension by the Canadian state in the market place and not self-limitation as others might suggest. 9 | DISCUSSION AND EMERGING ISSUES Dentchev et al (2015) have systematically shown that the literature on the role of government in CSR has in recent years steadily grown, but the topic remains insufficiently addressed. Hence, there is a need to avoid underestimating the importance of the quasi-mandatory side of CSR (Konrad et al, 2008).…”
Section: Governmental Programs and The Canadian National Csr Stratementioning
confidence: 99%
See 3 more Smart Citations
“…Thus, we are witnessing a case of self-extension by the Canadian state in the market place and not self-limitation as others might suggest. 9 | DISCUSSION AND EMERGING ISSUES Dentchev et al (2015) have systematically shown that the literature on the role of government in CSR has in recent years steadily grown, but the topic remains insufficiently addressed. Hence, there is a need to avoid underestimating the importance of the quasi-mandatory side of CSR (Konrad et al, 2008).…”
Section: Governmental Programs and The Canadian National Csr Stratementioning
confidence: 99%
“…As such, Gond, Kang, and Moon (2011, p. 641) have argued that the role of government in CSR has not received significant attention since analysis of the 'CSR-government relationship' is largely counter-intuitive to many. Thus, by definition, CSR precludes a role for government (Dentchev, Haezendonck, & van Balen, 2015;Gjølberg, 2010). Thus, by definition, CSR precludes a role for government (Dentchev, Haezendonck, & van Balen, 2015;Gjølberg, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This commentary builds on a wide body of literature that focuses on the interactions between government, business, and society; and it categorizes these players into three types, accordingly [39][40][41][42][43][44]. The commentary highlights the way in which a better understanding of those interactions can be useful in the context of addressing resource hotspots.…”
Section: Players Are Interconnected and Multi-dimensionalmentioning
confidence: 99%